Beneficial Effects of Low Iron Contents on Cobalt‐Containing Spinel Catalysts in the Gas Phase 2‐Propanol Oxidation. Issue 18 (25th August 2022) - Dreyer, Maik; Hagemann, Ulrich; Heidelmann, Markus; Budiyanto, Eko; Cosanne, Nicolas; Ortega, Klaus Friedel; Najafishirtari, Sharif; Hartmann, Nils; Tüysüz, Harun; Behrens, Malte
Abstract: Oxidation reactions are highly relevant transformation reactions in the industry. Mixed Co and Fe containing oxides are promising substituents for noble‐metal‐based catalysts due to lower cost and higher thermal stability. Performing oxidation catalysis in the liquid phase is desired to prevent total oxidation. An approach toward liquid phase reactions is water vapor added to the gas stream, which can help to build an experimental bridge between both phases. Here, nanocasted Co3‐x Fex O4 spinels are studied in the gas phase oxidation of 2‐propanol as a probe for selective oxidation without and with the addition of water into the reaction feed. In both cases, low amounts of Fe (≤4 %) were found to be beneficial for the activity. Under wet conditions, there is a negative effect on the activity below 150 °C during heating due to competitive adsorption. However, at higher temperatures during cooling, the activity is higher due to a slower deactivation. Abstract : 2‐Propanol oxidation : Co and Fe spinel catalysts were tested in the gas phase oxidation of 2‐propanol and a beneficial effect of doping on the activity was found. When adding water to the gas stream, the activity at low temperatures during heating decreases due to competitive adsorption, while also the deactivation speed decreases which leads to a higher activity during cooling.